The improvement of meat nutrient composition in broiler chickens fed diets containing rice bran tempeh supplemented with cellulose - U. Santoso; B. Brata; K. Kususiyah; M. Dani (Diponegoro University, 2023)
This study was aimed to evaluate the effect of cellulase supplementation in diets containing rice bran tempeh on body conformation, fat deposition, nutritional composition of broiler meat and blood biochemical concentrations in broiler chickens. This research was carried out for 3 weeks from 15 days to 35 days of age. Two hundred broilers aged 15 days were divided into 4 treatment groups with 5 replications (8 broilers for each replication) for each treatment, as follows: T1 = 0% cellulase; T2 = 0.05% cellulase; T3 = 0.1% cellulase, and T4 = 0.15% cellulase. Body conformation, chemical meat composition, fat deposition, blood pH, glucose and uric acid were measured. The addition of 0.05% or 0.15% cellulase significantly reduced leggedness (P<0.05), whereas 0,1% or 0,15% cellulase addtion significantly reduced the content of meat fat and ash plus carbohydrate. In addition, the inclusion of 0.05% cellulase increased the content of meat protein (P<0.01). The inclusion of cellulase from 0.05-0.15% did not decrease fat deposition, blood concentration of uric acid, cholesterol, glucose and pH. In conclusion, the addition of 0.1% or 0.15% cellulase improved meat nutrient composition without improving body conformation.